PENGARUH METODE PEMBELAJARAN AKTIF TIPE CARD SORT TERHADAP HASIL BELAJAR PPKn PADA SISWA KELAS IV SD NEGERI 14 BIRU KABUPATEN BONE - YUSMARANI, YUSMARANI (Global Journal Teaching Professional, 2024)
This research is a quantitative type of quasi-experimental research which aims to determine whether or not there is an influence of the use of card sort type active learning methods on the PPKN learning outcomes of class IV students at SD Negeri 14 Biru, Bone Regency. The variables in this research are active learning media type card sort (independent variable), and PPKN learning outcomes (dependent variable). The research population was all fourth grade students at SD Negeri 14 Biru, Bone Regency, totaling 42 students. This research uses a saturated sampling technique, namely class IVA for the experimental class and IVB for the control class. Research data was obtained by giving a multiple choice test. The pretest learning results in the experimental class were in the poor category with a mean of 55,60 with a percentage of 24.00%, while in the control class the results were obtained in the poor category with a mean of 41%, a percentage of 40%. The posttest learning results in the experimental class were in the good category, with a mean of 52.29 with a percentage of 20.00%, while in the control class they were in the poor category with a mean of 52.29, a percentage of 20%. The data collection technique uses multiple choice tests. The data analysis technique is inferential statistical testing using the Independent